Performance characteristics in transonic axial compressor rotor blade using circular jets - Epsipha, Pauline (2016)
The reduction of the flow separation region or even eliminating it from the transonic axial flow compressor has been a motivating research area as it reduces turbulence and modifies the flow field into more desired state. Even a small performance improvement could be a big help in saving fuel cost. Several active and passive flow control options were established and one among them is synthetic jet. Synthetic jet provides unsteady momentum to the flow field without net mass injection. Synthetic jets with slot orifice are previously investigated in transonic level study for its efficiency enhancement. Hence, a systematic numerical investigation was carried out to understand the impact of circular jets as continuous steady jet in transonic level study which is followed by time constrained synthetic jet (transient) for the analysis of flow control effectiveness. The seven and fourteen array of jet formation were placed at three positions specifically upstream, downstream and close to the flow separation point (25%, 50% and 75% of the blade span) at suction side of transonic compressor rotor blade. Two velocities such as 300m/s and 500 m/s were tested in all three jet position models to discover the superior separation control model and finally one reasonable model with better flow control effectiveness was used to run the time constrained synthetic jet approach for analyzing the flow field. High actuation velocity provided (500m/s) shows healthier variation in flow control compared to lower velocity (300m/s) due to its low momentum coefficient. In seven array jet formations, the jet flow fixed upstream the separation point (25% of blade span) controls the separation region more effectively while in fourteen array configuration, the jet placed at the midpoint of the blade span (close to separation point) enhances the separation control showing desirable flow control. However the vital part is that velocity distribution over the blade which reduces the flow separation in contradictory abundantly affects the total pressure ratio which also impacts adiabatic efficiency. Thus 4% of efficiency loss were calculated in seven array configuration and 13% of efficiency loss in fourteen array configuration. Comparative study over these models gives us the detailed analysis of flow field performance characteristics such as velocityvariation, 3D velocity streamline, pressure distribution, Mach number distribution, efficiency and total pressure ratio.